Islamic solution to the world's problems - Al'Mahdi, Muhammad (Kuala Lumpur : Saba Islamic Media, 2004)
This talk offer a solution to the diseased society of today world. It covers the understanding of the laws of learning by which all human development take place; positive, accurate and motivational worldview etc.
Title from title screen
Host: Dr. Muhammad Al'Mahdi
Keywords: Islamic sociology